Measuring Growth in Total Factor Productivity - Ghosh, Swati R.; Kraay, Aart (World Bank, Washington, DC, 2012)
Gains in total factor productivity (TFP) reflecting more efficient use of inputs, have long been recognized as an important source of improvements in income and welfare. Cross-country differences in income levels and growth rates are mostly due to differences in productivity. Measuring TFP is therefore important in assessing countries' past and potential economic performance. But it is also difficult. This note discusses some of the difficulties using data for the Republic of Korea in 1960-70 for illustration.